Quality of Life among Infertile Women Attending an Infertility Treatment Center, Kathmandu - Pradhan Shrestha, Subhadra; Bhandari, Sushila Devi; Pradhan, Sushaili (Journal of Nepal Health Research Council, 2020)
Background: The problem of infertility is an increasing issue worldwide, among married reproductive age couples, particularly women. Infertility can affect every aspect of quality of life among infertile women. This study aimed to assess the quality of life of infertile women attending an infertility treatment center.Methods: A crossectional  study of 385 infertile women age 25-50 years attending an infertility treatment center was carried out from 8th July 2018 to 4th January 2019. Data were collected using the Short Form Health Survey (Rand SF-36), containing 36 questions by interview technique and analyzed using descriptive and inferential statistics.Results: The higher proportion (63.38%) of primary infertility was involved in this study compared to secondary infertility without baby (24.93%) and with the baby (11.69%). More than half (54.5%) of infertile women had low-level quality of life whereas 45.5% of them had a high level of quality of life. The mean scores of quality of life subscales were not significantly different between primary and secondary infertility (p-value >0.05). There was no statistically significant association between socio-demographic variables and quality of life of primary and secondary infertility (p-value >0.05). There was a statistically significant difference between the duration of infertility and quality of life of primary and secondary infertility with baby (p-value 0.020), and between the reason of infertility and quality of life of secondary infertility without a baby (p-value 0.010).Conclusions: A high proportion of infertile women had low-level quality of life. Therefore, it is necessary to provide them information, education, and counseling regarding infertility.Keywords: Infertility treatment center; infertile women; quality of life